Spectral analysis of Deccan intrabasaltic bole beds: Implications for the formation and alteration of phyllosilicates on Mars. (January 2017) - Craig, Patricia; Chevrier, Vincent; Sayyed, M.R.G.; Islam, R.
Abstract: To fully understand phyllosilicates on Mars, it is beneficial to study analog deposits on Earth. One attractive candidate for martian phyllosilicates is the intrabasaltic bole beds (palaeosols) from the Deccan Volcanic Province of India. Eleven samples from the upper-layer red Deccan bole beds and underlying yellow and green Deccan bole beds were analyzed by X-ray diffraction (XRD), near-infrared (1.0–2.5 µm) and mid-infrared (5–15 µm) reflectance spectroscopy. Analysis of the bole beds indicated that the red boles are composed of a mixture of montmorillonite and hematite, yellow boles contain vermiculite and minor montmorillonite and green boles are composed mainly of nontronite (smectite) and celadonite (mica). While the bole beds are all chemically similar to each other and to the underlying basalt from which they were weathered, they are mineralogically different. This suggests transformation from one mineral to the next without ion transfer or loss which could be indicative of a limited-water environment. In fact, celadonite can transform into smectites (such as montmorillonite), often with vermiculite as an intermediate step. This not only explains the stratigraphy and mineralogy of the Deccan bole beds but may also explain the layered phyllosilicates identified in various, global locations on Mars. The transition observed in the Deccan bole beds suggests an evolution of the alteration process from deuteric alteration to low-temperature weathering, likely due to changes in temperature, in a closed system (no significant ion transfer) as evidenced by the minerals' similar chemistry. Thus, the Deccan bole beds are a good analog for the phyllosilicates layers on Mars and by studying the chemistry, mineralogy and spectral properties of the Deccan bole beds, we can link their formation and alteration processes to those of martian phyllosilicates. This will provide a clearer understanding of the environmental conditions on Mars at the time of the phyllosilicates' formation and hence during Mars' earliest history. Highlights: Deccan palaeosols were analyzed using XRD, near- and mid-infrared spectroscopy. The evolution is the transformation of celadonite into vermiculite then smectites. The Deccan bole beds stratigraphy is similar to that of Mawrth Vallis, Mars. Mineral paragenesis in Mawrth Vallis may result from shifts in formation processes. Processes include deuteric to low-temperature weathering with limited ion loss.